Pengaruh Penyangga Modal dan Ukuran Perusahaan terhadap Keputusan Pembagian Dividen dengan Cadangan Kerugian Penurunan Nilai sebagai Variabel Moderasi pada Emiten Perbankan - Ricardo Parulian Sibagariang; Andri Zainal; Jufri Darma; Chandra Situmeang; Arfan Ikhsan; Dedy Husrizal Syah (Jurnal Riset Akuntansi, 2026)
The banking sector faces dual challenges from economic turbulence and the implementation of expected credit loss accounting standards. An empirical anomaly has emerged where large-scale banks remain aggressive in distributing dividends despite soaring provisioning burdens, while medium-scale banks tend to retain earnings. This research aims to analyze the effect of capital buffer and firm size on dividend distribution decisions, while examining the ability of allowance for impairment losses to moderate these interactions. Utilizing a causal explanatory panel data design, this study observed 15 banking entities on the Indonesia Stock Exchange from 2020 to 2024. Data analysis was conducted using the Tobit regression model to accommodate dividend data characteristics left-censored at zero. Results prove that the capital buffer has no significant effect on dividend decisions, confirming the conservative posture of banks in prioritizing capital retention as a risk cushion. Conversely, firm size significantly determines profit distribution policy positively. In the moderation test, allowance for impairment losses does not moderate the capital buffer-dividend relationship but significantly moderates and amplifies the positive effect of firm size on dividend decisions. These findings imply a strategic resilience signaling maneuver, where large banks respond to high provisioning by expanding cash distribution to prove fundamental robustness to the market. Practically, this study recommends investors prioritize large-scale banks for stable returns and provides insights for regulators regarding the urgency of more adaptive regulatory adjustments.